2005
DOI: 10.1002/chin.200515069
|View full text |Cite
|
Sign up to set email alerts
|

N‐Halosuccinimide/BF3—H2O, Efficient Electrophilic Halogenating Systems for Aromatics.

Abstract: Aromatics. -N-halosuccinimide/BF3·H2O mixtures are found to be efficient reagents for halogenation of deactivated arenes. DFT theoretical calculations show that superelectrophilic reagents are generated by multiple protonation of the N-halosuccinimides under the present conditions. -(PRAKASH*, G. K. S.; MATHEW, T.; HOOLE, D.; ESTEVES, P. M.; WANG, Q.; RASUL, G.; OLAH, G. A.; J. Am. Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…However, by traditional chemical synthesis, halogenations are generally not environmentally friendly reactions because most of these reactions need to be carried out under harsh conditions and often involve the use of toxic reagents, catalysts and solvents. Chemical halogenation reactions also lack regioselectivity, resulting in many byproducts (10)(11)(12)(13). The use of enzymes i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, by traditional chemical synthesis, halogenations are generally not environmentally friendly reactions because most of these reactions need to be carried out under harsh conditions and often involve the use of toxic reagents, catalysts and solvents. Chemical halogenation reactions also lack regioselectivity, resulting in many byproducts (10)(11)(12)(13). The use of enzymes i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Selective C-H activation is essential 1 for the synthesis of bioactive molecules [2][3][4] and natural products [5][6][7][8][9][10][11][12][13] , medicinal chemistry 3,[14][15][16][17] , the materials industry [18][19][20] , and agricultural industry [21][22][23] . Synthetic routes to activate unreactive C-H bonds require harsh conditions 24 and usually show poor selectivity 25 owing to the high C-H bond dissociation energy and its inertness due to low polarity 26 . Biological systems, such as non-heme iron enzymes, [27][28][29][30][31][32][33][34] carry out selective C-H activation of unreactive C-H bonds [35][36][37][38][39][40][41] efficiently at ambient conditions to catalyze a wide variety of reactions 37,[42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…We could either brominate the final molecule PF‐622 or use 4‐bromophenyl isocyanate as a starting material to synthesize a halide precursor 7 of PF‐622 . There are several halogenation methods available in literatures . Some of the methods were tried and did not introduce halogen only into the phenyl ring A of the final molecule PF‐622 .…”
Section: Resultsmentioning
confidence: 99%
“…There are several halogenation methods available in literatures . Some of the methods were tried and did not introduce halogen only into the phenyl ring A of the final molecule PF‐622 . Krishna and her coworkers reported that an aniline and anisole can be brominated by the electrophilic substitution of bromine‐generated in situ from ammonium bromide as a bromine source and hydrogen peroxide as an oxidant.…”
Section: Resultsmentioning
confidence: 99%